Policy translation and implementation research of community-based stunting prevention programs at the village level - Indrawati Aris Tyarini; Darmi Arda (Lembaga Edukasi Ilmiah Indonesia, 2026)
Introduction: Community-based stunting prevention remains a major challenge in decentralized health governance systems due to variations in policy translation and implementation at the village level. This study aimed to analyze factors influencing the implementation effectiveness of community-based stunting prevention programs. Methods: A quantitative cross-sectional analytical study was conducted in selected rural villages in Eastern Indonesia between January and April 2026. A total of 130 respondents were selected using proportional stratified random sampling. Data were collected through structured questionnaires and analyzed using descriptive statistics, chi-square tests, and multivariate logistic regression with a significance level of α = 0.05. Results: Strong institutional coordination was the most dominant factor associated with effective implementation of stunting prevention programs (AOR = 3.76; 95% CI: 1.72–8.19; p < 0.001). Good policy communication (AOR = 2.84; 95% CI: 1.31–6.15; p = 0.008), high community participation (AOR = 2.57; 95% CI: 1.18–5.60; p = 0.017), adequate implementer capacity (AOR = 2.21; 95% CI: 1.03–4.76; p = 0.041), and sufficient resource availability (AOR = 2.69; 95% CI: 1.22–5.95; p = 0.014) also significantly improved implementation effectiveness. Conclusion: Effective stunting prevention requires adaptive governance systems emphasizing multisectoral coordination, community participation, and context-sensitive policy implementation at the village level.